La sociedad por acciones simplificada: una nueva estructura para hacer negocios en las Américas - Tramhel, Jeannette M. E. (2017)
This article is an introduction to the OAS Model Law on the Simplified Corporation (SAS). As a simple and easy alternative corporate form that reduces complexity and hence, also the cost, the SAS extends the availability of incorporation to all business operations, particularly MSMEs, and so serves an important function in encouraging formalization. The article reviews the benefits associated with formalization, simplification of the process of business registration, and explains key elements of the Model Law in light of emerging global best practices.